1985
DOI: 10.1136/gut.26.8.825
|View full text |Cite
|
Sign up to set email alerts
|

What is the significance of pancreatic ductal mucinous hyperplasia?

Abstract: SUMMARY The prevalence, distribution, and clinical associations of pancreatic ductal mucinous hyperplasia were studied in 102 non-malignant pancreases. Ductal mucinous hyperplasia was found in over 60% of specimens and was frequently associated with increased fibrosisoccasionally resembling pancreatitis. Significantly more ductal mucinous hyperplasia was found in pancreas from patients who were receiving corticosteroid treatment. Neither a history of hypercalcaemia in the three months before death, diabetes me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These changes promote the formation of intraluminal protein gel or plugs, which are early histological features of chronic pancreatitis [78]. Intraductal obstruction can lead to pancreatic atrophy, ductal mucinous hyperplasia [79, 80], Goblet-cell metaplasia and perhaps pancreatic stone formation [77]. …”
Section: Cftr Dysfunction In Pancreatitismentioning
confidence: 99%
“…These changes promote the formation of intraluminal protein gel or plugs, which are early histological features of chronic pancreatitis [78]. Intraductal obstruction can lead to pancreatic atrophy, ductal mucinous hyperplasia [79, 80], Goblet-cell metaplasia and perhaps pancreatic stone formation [77]. …”
Section: Cftr Dysfunction In Pancreatitismentioning
confidence: 99%
“…In our study, the prevalence rates of PanINs fell within these ranges. In contrast, the prevalence rates of PanIN‐1 and PanIN‐3 in patients without pancreatic adenocarcinoma ranged from 15.5% to 82% and from 0% to 3.4%, respectively . There was no difference in the frequency of PanIN‐1 between patients with and without invasive ductal carcinoma.…”
Section: Discussionmentioning
confidence: 79%
“…Many studies have reported on the frequency of PanIN lesions in patients with or without invasive ductal carcinoma . However, there have been no reports about the relationship between PanIN in invasive ductal carcinoma and prognosis.…”
Section: Discussionmentioning
confidence: 99%